UPLC-MS/MS-Based Serum Metabolomics Signature as Biomarkers of Esophagogastric Variceal Bleeding in Patients With Cirrhosis - Ai, Yingjie; Huang, Xiaoquan; Chen, Wei; Wu, Ling; Jiang, Siyu; Chen, Ying; Chen, Shiyao (Frontiers in Cell and Developmental Biology, 2022)
Background Esophagogastric variceal bleeding (EVB) is a common and ominous complication of cirrhosis and represents the degree of portal hypertension progression and cirrhosis decompensation, desiderating investigation into sensitive and specific markers for early detection and prediction. The purpose of this study is to characterize unique metabolites in serum of cirrhotic EVB patients and identify potential noninvasive biomarkers for detecting and assessing risk of variceal bleeding and cirrhosis progression through metabolomics-based approaches, as well as explore possible pathophysiological mechanisms. Methods We used ultra-performance liquid chromatography coupled to tandem mass spectrometry (UPLC-MS/MS) to profile serum metabolome. In one discovery cohort (n=26, 13 cases of EVB), univariate and multivariate statistical analyses were performed to demonstrate separation between two groups and identify differentially expressed metabolites. Potential biomarkers were screened by Boruta and logistic regression analysis, further evaluated by receiver operating characteristic analysis and tested in two validation cohorts (n=34, 17 cases and n=10, 5 cases). Results Bioinformatic analyses demonstrated that EVB patients possessed distinct metabolic phenotypes compared with nEVB controls, characterized by 7 elevated and 6 downregulated metabolites, indicating that EVB-related metabolic disturbance might be associated with vitamin metabolism and fatty acid metabolism. Eight potential biomarkers were selected among which citrulline and alpha-aminobutyric acid with moderate AUC values, tested in the validation cohorts, were identified as specific biomarkers of EVB. Conclusion Our metabolomic study provides an overview of serum metabolic profiles in EVB patients, highlighting the potential utility of UPLC-MS/MS based serum fingerprint as a feasible avenue for early detection of EVB.